PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OFFER, RETURN ON ASSET DAN INFLASI TERHADAP RETURN SAHAM - Keysha Azahra; Rizal Riyadi; Didit Pradipto (Strategic: Journal of Management Sciences, 2025)
This study focuses to analyze the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Assets (ROA), and inflation on stock returns in pharmaceutical companies listed on the Indonesia Stock Exchange during the 2018–2023 period. The research employs a multiple linear regression analysis approach using secondary data from company financial reports. The findings indicate that CR, DER, and ROA have a significant impact on stock returns, while TATO and inflation do not exhibit a significant effect. Simultaneously, all independent variables contribute to changes in stock returns. These findings provide insights for investors in evaluating financial factors that influence stock returns in the pharmaceutical sector. Future research is recommended to expand the scope of variables to enhance the accuracy of stock return prediction models.